Las especies de pulgones del maiz - Pons, X.=700 1 Asin, L.; Comas, J.; Albajes, R.
(Es, En)
ilus., 17 ref.
Keywords: MAIZ; APHIDIDAE; METOPOLOPHIUM DIRHODUM; RHOPALOSIPHUM PADI; SITOBION AVENAE; ESPAÑA; PULGONES